Japón: la herencia política de Fumio Kishida - Kerber Palma, Víctor (El Colegio de México A.C., 2024)
The work provides an overview of Japan’s current domestic and foreign policy situation since Prime Minister Fumio Kishida took office. Kishida presides over an ageing society reopening after the Covid-19 pandemic and in shock over the assassination of former Prime Minister Shinzō Abe. He has also faced challenges posed by China and the two Koreas, as well as the aftermath of the Fukushima nuclear accident plant, which resulted in the release of contaminated wastewater. The successes and failures are reflected in the fluctuating popularity ratings of the Kishida cabinet.